Comparative analysis of calculation models of soil behavior on the example of the tray experiment`s modeling - Vynnykov, Yuriy; Razdui, Roman (Academic journal Industrial Machine Building Civil Engineering, 2022)
Graphs of settlements of stamp experiment in the modeling of the tray experiment with variable reinforcement parameters to determine the effect of reinforcement with vertical soil-cement elements (SCE) of weak clay bases of strip foundations of buildings are shown. The simulation results of the experiment using the Mohr-Coulomb ideal elastoplastic model of soil behavior and the Hardening soil model isotropic compaction model of soil behavior by the finite element method for estimating the stress-strain state of the "soil-cement base – rigid strip stamp" system when using different models of the SCE assignment are presented. A comparison of the methods of modeling the stress-strain state with the capabilities of the Plaxis 3D software package is carried out. The most optimal models of soil behavior for the simulation of SCE under existing soil conditions have been determined
Keywords: vertical soil-cement element; soil base; settlement; comparison of calculation methods; finite element method; tray experiment